MANAJEMEN PRODUKSI PROGRAM WAJAH DESA DALAM MEMPROMOSIKAN DESA-DESA DI KABUPATEN BENGKALIS DI BENGKALIS TV - Ternado A, Leo; Rimayanti, Nita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The development of communication and informatics technology makes television as one of the most attractive tools to be enjoyed. Broadcasting as a channel of information and forming public opinion, its role is more strategic, especially in developing democratic life. Village face is an informative-based program that presents information about the activities and the potential of villages in Bengkalis District such as public servants in the village, village geographic and demographic conditions, village tourism, economy, village development and village activities.Wajah Desa is a documentary program.Village face is broadcasted by a local television station in Bengkalis District, Bengkalis TV, which is a private station owned by PT. Riau Media Television (RTV), which is headquartered at Pekanbaru. Wajah Desa program aims to promote villages in Bengkalis District to the community, especially the people at Bengkalis, this program is broadcasted on Bengkalis TV and also uploaded on Bengkalis TV youtube channel. The purpose of this study was to determine the production management wajah desa in promoting villages in Bengkalis disctrict on Bengkalis TV.This study used a qualitative descriptive research method. Data collection techniques used in this study are observation, interviews, and documentation. The subjects involved in this study were determined based on the purposive technique consisting of the person in charge of the operations of TV Bengkalis, cameramen, scriptwriters, editors and dubbers. Data analysis techniques were carried out by using the interactive data analysis model Miles and Huberman with data validity checking techniques, that is an extension of participation and triangulation.The results of this study the Wajah Desa program to apply 3 stages in the production process, namely: (1) pre-production was carried out in 7 forms, which is ideas or thoughts, program objectives, script writing, team formation and team meetings, costs, facilities and infrastructure, production time. (2) production, in the process the production, Wajah Desateam took pictures in the field and used lighting from sunlight and used the existing sound mic at the camera of Bengkalis TV. (3) post production, this stage consists of four forms, which is visual capture from the camera, online editing, mixing, broadcasting. The whole process is a form of management in the production process of the Wajah Desa program.